Editorial: Aquaculture-aided approaches for conservation and sustainable fisheries - Matthew D. Taylor; Alistair Becker; Edward V. Camp; Luis Henríquez-Antipa; Neil R. Loneragan; Kai Lorenzen (Fisheries Research, 2026)

Time-series transcriptomics sheds light on the rapid and dynamic response of the moss Physcomitrium patens to salt stress - Armin Horn; Chandra Shekhar Misra; José Miguel Sordo; Jennifer Catherine Nascimento Schulze; Omar Vergara-Díaz; Rubén Vicente; Henrik Toft Simonsen; Jörg D. Becker (Journal of Plant Physiology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

To stock or not to stock: The paradox of releasing fish and invertebrates in estuaries - Neil R. Loneragan; Matthew D. Taylor; Zhongxin Wu; Alan Cottingham; Ryan W. Schloesser; Nathan P. Brennan; Brian Poh; Kerry Trayler; Alistair Becker; James R. Tweedley (Fisheries Research, 2026)

Fundamental evolved motives meet environmental threats and opportunities - D. Vaughn Becker; Douglas T. Kenrick; Steven L. Neuberg; Michael E.V. Varnum; Jill M. Sundie; Cari M. Pick; Oliver Sng; Keelah E.G. Williams; Ahra Ko; Joshua M. Ackerman; Jamie Arona Krems; Vladas Griskevicius; et al. (Evolution and Human Behavior, 2026)

Valid and Reliable Questionnaire for Assessing Nutrition and Physical Activity Practices in Early Care and Education - Christina M. Becker; Janice Kao; Sridharshi C. Hewawitharana; Carolyn D. Rider; Amanda Linares; Ron Strochlic; Miranda Westfall Brown; Gail Woodward-Lopez (Journal of Nutrition Education and Behavior, 2026)

Corrigendum to “Fundamental evolved motives meet environmental threats and opportunities” Evolution and Human Behavior, 47, Issue 4, 106860 - D. Vaughn Becker; Douglas T. Kenrick; Steven L. Neuberg; Michael E.V. Varnum; Jill M. Sundie; Cari M. Pick; Oliver Sng; Keelah E.G. Williams; Ahra Ko; Joshua M. Ackerman; Jamie Arona Krems; Vladas Griskevicius; et al. (Evolution and Human Behavior, 2026)

Polyphasic Taxonomy of Species within the Dermatophyte Genus Arthroderma Including A. fimbriatum sp. nov and A. cellare sp. nov - Frederik Baert; Paulien Lefevere; Goens Karine; Roelke De Paepe; Elizabet D’hooge; Pierre Becker; Ann Packeu (Mycopathologia, 2026)

Region- and season-specific exposure to lead in a common North American songbird - M. L. Ohrberg; D. J. Becker; G. M. Filippelli; E. D. Ketterson; S. T. Rader; S. M. Reed; E. J. Williams; A. E. Jahn (Ecotoxicology, 2026)
Although birds have been used globally as bioindicators of heavy metals, the determinants and physiological consequences of their exposure to heavy metals remain poorly understood. The American Robin ( Turdus migratorius ) is a common songbird in a variety of habitats across most of North America that could serve as an ideal sentinel of heavy metal contamination. We evaluated how robin exposure to lead (Pb) varied regionally, seasonally and among demographic groups, and assessed impacts on body condition and reproductive hormone concentrations. We detected higher blood Pb concentrations in robins sampled in a more urban region (Indiana) compared to a more rural region (Alaska). Higher blood Pb concentrations in the more urban region may reflect the robin diet of earthworms, which accumulate lead due to their feeding behavior and could incorporate greater ambient soil lead contamination typical of more urban areas. Blood Pb concentrations were also highest in spring and summer, when robins primarily forage on earthworms. We found no relationship between blood Pb concentrations and body condition, but blood Pb concentrations showed a negative relationship with testosterone in male robins and with estradiol in female robins, suggesting lead may have negative effects on reproductive function. Overall, these results suggest that robins could serve as reliable bioindicators of lead and its impacts on wildlife health across a broad range of ecosystems.

Acoustic telemetry reveals predation rates on mulloway (Argyrosomus japonicus) stocked into a south-east Australian estuary - Alistair Becker; D. Stewart Fielder; Jason D. Thiem; Matthew.D. Taylor (Fisheries Research, 2026)

Ecology of community reassembly: Movements and diets of megafauna during a decade of restoration in Mozambique - Matthew C. Hutchinson; Reena H. Walker; Joel O. Abraham; Justine A. Becker; Dominique D. Gonçalves; Ciara M. Nutter; Johan Pansu; Erin M. Phillips; Arjun B. Potter; Beto Soares Tenente; Marc E. Stalmans; Ryan A. Long; et al. (Ecology, 2026)
The last decade has brought a worldwide surge of interest in rewilding—the repopulation of large herbivores and carnivores—as a strategy for conserving species and reviving ecosystem functions. Rewilding initiatives, if closely monitored, can provide unique insights into the ecology of the world's largest animals at otherwise impossible spatial and temporal scales. Capitalizing on these opportunities, and developing a knowledge base to guide future restoration efforts, requires the collection and dissemination of long‐term data that document community reassembly. To date, such data are virtually nonexistent: most megafaunal restoration projects are nascent and/or have not been rigorously monitored. Since 2008, the Gorongosa Restoration Project, in Mozambique's Gorongosa National Park, has facilitated the recovery of megafauna populations that were severely depleted or extirpated during the country's civil war (1977–1992). For over a decade, we have monitored Gorongosa's large‐herbivore populations to understand how animal behavior and trophic interactions change as communities reassemble. Here, we present spatiotemporally explicit data sets on the movements and diets of large herbivores in Gorongosa between 2013 and 2025, along with annual rainfall data. This period encompassed extremes of climate (including some of the driest and wettest years on record) and the reintroduction, starting in 2018, of locally extinct apex predators and scavengers: African wild dog ( Lycaon pictus ), leopard ( Panthera pardus ), spotted hyena ( Crocuta crocuta ), and side‐striped jackal ( Lupulella adusta ). We used GPS telemetry to monitor 277 herbivores of seven species (listed below with number of individuals collared, median duration of tracking, and median number of locations per individual): Cape bushbuck ( Tragelaphus sylvaticus : 103 individuals; 280 days; 6646 fixes), nyala ( T. angasii : 37 individuals; 306 days; 6789 fixes), greater kudu ( T. strepsiceros : 80 individuals; 300 days; 17,365 fixes), common eland ( T. oryx : 10 individuals; 334 days; 15,783 fixes), waterbuck ( Kobus ellipsiprymnus : 22 individuals; 13 days; 2877 fixes), plains zebra ( Equus quagga : 7 individuals; 212 days; 1171 fixes), and African savanna elephant ( Loxodonta africana : 18 individuals; 706 days; 33,122 fixes). For 295 individuals that were immobilized during this work, we present morphological measurements (chest girth, body length, hind‐foot length, weight), reproductive status and nutritional condition (ultrasound measurements, palpation scores), and fate (mortality date and cause, if known). For diet analysis, we used DNA metabarcoding to identify and quantify the relative abundances of plant taxa in 3785 fecal samples from 27 mammal species belonging to 11 families and 7 orders. In all, we recorded 516 food‐plant taxa from at least 87 plant families and 39 orders. For Gorongosa's 15 most common large herbivores, the median sampling depth was 216 fecal samples per species (interquartile range 156–279); the overall median sampling depth was 92 samples per species (range 1–499). We include basic metadata collected in the field (e.g., date, time, GPS location, animal sex, and age) along with laboratory notes and information on plant taxonomic identification. These data are valuable not just as a window on one ecosystem's recovery from armed conflict, but also as a resource for macroecology, meta‐analysis, and synthetic studies of animal movement, diet, and the dynamics of community reassembly. The data are freely available for use and this paper should be cited whenever data are reused; see Data : Metadata : Class III.B.4 for additional details.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Responsible restocking to aid recovery of an iconic sciaenid fishery: A case study of Mulloway (Argyrosomus japonicus) - Alistair Becker; Julian M. Hughes; Ashley M. Fowler; Matthew D. Taylor (Fisheries Research, 2026)

Hawaiian Monk Seal ( Neomonachus schauinslandi ) Marine Debris Entanglement Risk Varies With Size Class and Sex - Jason D. Baker; Thea C. Johanos; Hope Ronco; Tracy A. Mercer; Brenda L. Becker (Marine Mammal Science, 2026)

Using acoustic telemetry to inform standardisation of catch rates from passive fishing gear: A case study using dusky flathead (Platycephalus fuscus) - Hayden T. Schilling; James A. Smith; Daniel E. Hewitt; Alistair Becker; Charles Gray; Geoffrey Liggins; Nicholas L. Payne; Dylan van der Meulen; Matthew D. Taylor (Fisheries Research, 2025)

The smoke-detector principle of pathogen avoidance: A test of how the behavioral immune system gives rise to prejudice - Florian van Leeuwen; Bastian Jaeger; John Axelsson; D. Vaughn Becker; Lina S. Hansson; Julie Lasselin; Mats Lekander; Matti Vuorre; Joshua M. Tybur (Evolution and Human Behavior, 2025)

Signatures of Polar Vortex Weakening in the MLTI: A Review - V. L. Harvey; D. Aggarwal; E. Becker; M. Bittner; B. Funke; L. Goncharenko; J. Jia; R. Lieberman; H.-L. Liu; V. Maliniemi; A. Marchaudon; H. Nesse; et al. (Surveys in Geophysics, 2025)
This paper is a collaborative effort that originated at the International Space Science Institute Workshop on “Physical links between Weather and Climate in Space and the Lower Atmosphere” held 22–26 January 2024. Many scientists attended that workshop and contributed their expertise related to polar vortex impacts on upper atmosphere variability. This paper summarizes well-known and newly reported signatures of polar vortex weakening on mesosphere–lower-thermosphere (MLT) temperature, winds, composition, planetary waves, gravity waves, tides, and ionospheric foF2. A variety of observational and modeling results are shown and are consistent with previously published variations in the dynamical and chemical state of the MLT and ionosphere during weak vortex events. We present Superposed Epoch Analysis (SEA) of upper atmosphere diagnostics and phenomena where day 0 is the onset of major SSWs. We also present SEAs where day 0 is the onset of stratopause warmings followed by elevated stratopause events. Our goal in performing two SEAs is to test the sensitivity of 10 hPa versus 1 hPa winds to predict upper atmosphere variability. Results suggest that zonal winds and the semidiurnal migrating solar tide (SW2) in the MLT are more sensitive to zonal wind reversals at 1 hPa rather than 10 hPa. Alternatively, the non-migrating DW2 tide in the equatorial upper mesosphere is best predicted by planetary wave-1 amplitudes in the winter high-latitude upper stratosphere rather than zonal wind reversals. A notable aspect of both SEAs is extremely large event-to-event variability in all diagnostics. Thus, conclusions drawn based on any one event are less robust than those based on many events.

Sterol aminoacylation regulates conidiation and sclerotia formation in Aspergillus oryzae - Daisuke Yokokawa; Shunsuke Tatematsu; Makoto Imai; Yoshihiro Takara; Yusuke Saga; Frédéric Fischer; Hubert D. Becker; Harushi Nakajima; Tetsuo Kushiro (Fungal Biology, 2025)

Capture Probability of Blue Swimmer Crab ( Portunus armatus ) in Baited Traps and Implications for Trap Survey Design - Alistair Becker; Daniel D. Johnson; Hugh Pederson; Matthew D. Taylor (Fisheries Management and Ecology, 2025)
Fishery independent surveys provide valuable data for fisheries assessments that predominantly rely on trends in catch per unit effort (CPUE). Many crustacean fisheries are harvested using traps, so this gear is often used for fishery independent surveys. The areal sampling unit for baited traps is normally poorly understood, so surveys can be biased if sampling areas overlap. The blue swimmer crab ( Portunus armatus ) is an important commercial and recreational species distributed around the warm temperate and tropical coast of Australia, and stock management typically relies on catch data supplemented by independent surveys. Acoustic telemetry was used to track fine‐scale movements of 37 crabs in response to deployment of baited‐traps and to estimate probability of capture relative to distance from the trap. Traps attracted crabs from an initial distance up to 70 m, with most movements towards traps after dark. Capture probability increased with decreasing initial distance from a deployed trap. Despite this, the probability of capture was

Elucidation of Mechanisms Associated with Proline Metabolism and Redox Balance in Peanut Microsymbionts Exposed to Water Stress - A. L. Furlan; J. F. Villa; E. Bianucci; D. F. Becker (Journal of Soil Science and Plant Nutrition, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comparison of salting-out assisted liquid-liquid extraction to polymeric solid phase extraction for liquid chromatography tandem mass spectrometry of neonicotinoids insecticides and metabolites in wastewater: Occurrence and aquatic risk assessment - Joyce Cristale; Raquel Wielens Becker; Valdemar Luiz Tornisielo; Renato Falcão Dantas; Shannon Bartelt-Hunt; Sathaporn Onanong; Daniel D. Snow (Environmental Pollution, 2025)

Aquatic occurrence, fate and potential ecotoxicity of insecticide and fungicide residues originating from a biofuels production facility using pesticide-treated seeds - Jascika A.A. Maclean; Shannon Bartelt-Hunt; Daniel D. Snow; Josephus F. Borsuah; Raquel Wielens Becker; Moushumi Hazra (Journal of Hazardous Materials, 2025)

Environmental contaminants assessment for frequently harvested migratory waterfowl in the Northeast Atlantic flyway - David B. Dayan; Brenda J. Hanley; Joshua Stiller; Wayne Richter; Ian D. Gregg; Nate R. Huck; Min T. Huang; Theodore C. Nichols; Henry M. Spliethoff; Jesse C. Becker; Lisa A. Murphy; Krysten L. Schuler (Science of The Total Environment, 2025)

Hemoplasma in melon-headed whale (Peponocephala electra, Gray, 1846), Veracruz, Mexico - Gerardo.G. Ballados-González; Juan Casas-Paul; Maria del Carmen C. Ruiz-Murillo; Graciela I. Bernal-Trejo; Kurt Navarro-Castañeda; Marco D. Perez-Medina; Roberto Ibarra-Laclette; Anabel Cruz-Romero; Arturo Serrano; Celina Naval-Ávila; Miguel A. Lammoglia-Villagómez; Estefanía Grostieta; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Computations of energetic nearshore waves: Are weakly dispersive phase-resolving models telling the same story? - Assaf Azouri; Volker Roeber; Martin D. Guiles; Mark Merrifield; Janet Becker; Douglas S. Luther (Coastal Engineering, 2024)

Evaluating the reproducibility of a deep learning algorithm for the prediction of retinal age - Jay Rodney Toby Zoellin; Ferhat Turgut; Ruiye Chen; Amr Saad; Samuel D. Giesser; Chiara Sommer; Viviane Guignard; Jonas Ihle; Marie-Louise Mono; Matthias D. Becker; Zhuoting Zhu; Gábor Márk Somfai (GeroScience, 2024)
Recently, a deep learning algorithm (DLA) has been developed to predict the chronological age from retinal images. The Retinal Age Gap (RAG), a deviation between predicted age from retinal images (Retinal Age, RA) and chronological age, correlates with mortality and age-related diseases. This study evaluated the reliability and accuracy of RA predictions and analyzed various factors that may influence them. We analyzed two groups of participants: Intravisit and Intervisit, both imaged by color fundus photography. RA was predicted using an established algorithm. The Intervisit group comprised 26 subjects, imaged in two sessions. The Intravisit group had 41 subjects, of whom each eye was photographed twice in one session. The mean absolute test–retest difference in predicted RA was 2.39 years for Intervisit and 2.13 years for Intravisit, with the latter showing higher prediction variability. The chronological age was predicted accurately from fundus photographs. Subsetting image pairs based on differential image quality reduced test–retest discrepancies by up to 50%, but mean image quality was not correlated with retest outcomes. Marked diurnal oscillations in RA predictions were observed, with a significant overestimation in the afternoon compared to the morning in the Intravisit cohort. The order of image acquisition across imaging sessions did not influence RA prediction and subjective age perception did not predict RAG. Inter-eye consistency exceeded 3 years. Our study is the first to explore the reliability of RA predictions. Consistent image quality enhances retest outcomes. The observed diurnal variations in RA predictions highlight the need for standardized imaging protocols, but RAG could soon be a reliable metric in clinical investigations.

Promoting best practices in ocean forecasting through an Operational Readiness Level - E. Alvarez Fanjul; S. Ciliberti; J. Pearlman; K. Wilmer-Becker; P. Bahurel; F. Ardhuin; A. Arnaud; K. Azizzadenesheli; R. Aznar; M. Bell; L. Bertino; S. Behera; et al. (Frontiers in Marine Science, 2024)
Predicting the ocean state in a reliable and interoperable way, while ensuring high-quality products, requires forecasting systems that synergistically combine science-based methodologies with advanced technologies for timely, user-oriented solutions. Achieving this objective necessitates the adoption of best practices when implementing ocean forecasting services, resulting in the proper design of system components and the capacity to evolve through different levels of complexity. The vision of OceanPrediction Decade Collaborative Center, endorsed by the UN Decade of Ocean Science for Sustainable Development 2021-2030, is to support this challenge by developing a “predicted ocean based on a shared and coordinated global effort” and by working within a collaborative framework that encompasses worldwide expertise in ocean science and technology. To measure the capacity of ocean forecasting systems, the OceanPrediction Decade Collaborative Center proposes a novel approach based on the definition of an Operational Readiness Level (ORL). This approach is designed to guide and promote the adoption of best practices by qualifying and quantifying the overall operational status. Considering three identified operational categories - production, validation, and data dissemination - the proposed ORL is computed through a cumulative scoring system. This method is determined by fulfilling specific criteria, starting from a given base level and progressively advancing to higher levels. The goal of ORL and the computed scores per operational category is to support ocean forecasters in using and producing ocean data, information, and knowledge. This is achieved through systems that attain progressively higher levels of readiness, accessibility, and interoperability by adopting best practices that will be linked to the future design of standards and tools. This paper discusses examples of the application of this methodology, concluding on the advantages of its adoption as a reference tool to encourage and endorse services in joining common frameworks.

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Experiences of Registered Dietitian Nutritionists Employed in the Charitable Food Network - R. Becker; E. Witwer; D. Frable; K. Eck (Journal of the Academy of Nutrition and Dietetics, 2024)

Influence of crop-livestock integration on direct and indirect contributions of beef systems to food security - C. Battheu-Noirfalise; A. Mertens; H. Soyeurt; D. Stilmant; E. Froidmont; Y. Beckers (Agricultural Systems, 2024)

Interactions between White Sharks (Carcharodon carcharias) and artificial reefs along the east-coast of Australia - Alistair Becker; Paul A. Butcher; Stephen Morris; Curtis Champion; Victor M. Peddemors; Michael B. Lowry; Matthew D. Taylor (Fisheries Research, 2024)

Wire-snare bushmeat poaching and the large African carnivore guild: Impacts, knowledge gaps, and field-based mitigation - Matthew S. Becker; Scott Creel; Mwamba Sichande; Johnathan Reyes de Merkle; Ben Goodheart; Thandiwe Mweetwa; Henry Mwape; D. Smit; A. Kusler; Kambwiri Banda; Brian Musalo; Lengwe Mwansa Bwalya; et al. (Biological Conservation, 2024)

Long-term impacts of urban floodplain management and habitat restoration on lizard communities in a Sonoran Desert city - Jules T. Wyman; Aaron D. Flesch; Jennifer L. Becker; Philip C. Rosen (Ecological Engineering, 2023)

Out of the shadows: automatic fish detection from acoustic cameras - R. M. Connolly; K. I. Jinks; A. Shand; M. D. Taylor; T. F. Gaston; A. Becker; E. L. Jinks (Aquatic Ecology, 2023)
Efficacious monitoring of fish stocks is critical for efficient management. Multibeam acoustic cameras, that use sound-reflectance to generate moving pictures, provide an important alternative to traditional video-based methods that are inoperable in turbid waters. However, acoustic cameras, like standard video monitoring methods, produce large volumes of imagery from which it is time consuming and costly to extract data manually. Deep learning, a form of machine learning, can be used to automate the processing and analysis of acoustic data. We used convolutional neural networks (CNNs) to detect and count fish in a publicly available dual-frequency identification sonar (DIDSON) dataset. We compared three types of detections, direct acoustic, acoustic shadows, and a combination of direct and shadows. The deep learning model was highly reliable at detecting fish to obtain abundance data using acoustic data. Model accuracy for counts-per-image was improved by the inclusion of shadows (F1 scores, a measure of the model accuracy: direct 0.79, shadow 0.88, combined 0.90). Model accuracy for MaxN per video was high for all three types of detections (F1 scores: direct 0.90, shadow 0.90, combined 0.91). Our results demonstrate that CNNs are a powerful tool for automating underwater acoustic data analysis. Given this promise, we suggest broadening the scope of testing to include a wider range of fish shapes, sizes, and abundances, with a view to automating species (or ‘morphospecies’) identification and counts.

Assessment of rapid wastewater surveillance for determination of communicable disease spread in municipalities - Mohsen Asadi; Daniel Hamilton; Corwyn Shomachuk; Femi F. Oloye; Chantel De Lange; Xia Pu; Charles A. Osunla; Jenna Cantin; Seba El-Baroudy; Edgard M. Mejia; Branden Gregorchuk; Michael G. Becker; et al. (Science of The Total Environment, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Suitability of saltmarsh creeks as release locations for stocked Mulloway (Argyrosomus japonicus) - Alistair Becker; D. Stewart Fielder; Michael B. Lowry; Matthew D. Taylor (Estuarine, Coastal and Shelf Science, 2023)

Implications of habitat use and movement of stocked juvenile dusky flathead ( Platycephalus fuscus ) on stock enhancement release strategies - Alistair Becker; Hugh Pederson; Michael B. Lowry; D. Stewart Fielder; Matthew D. Taylor (Fisheries Management and Ecology, 2023)
Stocking of marine fish into coastal systems to augment natural recruitment is a growing practice adopted by fisheries managers around the world. Releasing fish directly into well‐resourced nursery grounds greatly increases survival and retention of stocked individuals but requires an understanding of juvenile habitat requirements. In eastern Australia, the dusky flathead ( Platycephalus fuscus ) is a highly regarded recreationally targeted species and the focus of an emerging stock enhancement programme, although little is known of their specific nursery habitat. Using acoustic telemetry, hatchery‐reared juveniles were monitored in Lake Macquarie to quantify habitat use and dispersal. Sandy areas adjacent to edges of seagrass beds were favoured, likely as foraging habitat. Within 5 weeks after release, fish were detected 5 km from the release site, but only at locations containing seagrass beds, so stocked fish likely disperse around estuaries to regions with suitable habitat. Future releases of dusky flathead should target areas containing patchy seagrass‐sand to optimise stocking outcomes. Beyond fisheries enhancement programmes, our findings highlight the importance of structured habitat, such as seagrass beds, for juvenile fish.

LP-36: The Clariant CompTox Suite – Towards implementation of predictive toxicology approaches to support discovery of chemical alternatives that are safe and sustainable by design - Q. Li; K. Addis; D. Becker; L. Bodelon; K. Framesqui; M. Hufnagel; A. Marson; F.A. Grimm (Toxicology Letters, 2023)

Correction: Regulatory dynamics of gene expression in the developing male gametophyte of Arabidopsis - Božena Klodová; David Potěšil; Lenka Steinbachová; Christos Michailidis; Ann-Cathrin Lindner; Dieter Hackenberg; Jörg D. Becker; Zbyněk Zdráhal; David Twell; David Honys (Plant Reproduction, 2023)

Regulatory dynamics of gene expression in the developing male gametophyte of Arabidopsis - Božena Klodová; David Potěšil; Lenka Steinbachová; Christos Michailidis; Ann-Cathrin Lindner; Dieter Hackenberg; Jörg D. Becker; Zbyněk Zdráhal; David Twell; David Honys (Plant Reproduction, 2023)
Sexual reproduction in angiosperms requires the production and delivery of two male gametes by a three-celled haploid male gametophyte. This demands synchronized gene expression in a short developmental window to ensure double fertilization and seed set. While transcriptomic changes in developing pollen are known for Arabidopsis , no studies have integrated RNA and proteomic data in this model. Further, the role of alternative splicing has not been fully addressed, yet post-transcriptional and post-translational regulation may have a key role in gene expression dynamics during microgametogenesis. We have refined and substantially updated global transcriptomic and proteomic changes in developing pollen for two Arabidopsis accessions. Despite the superiority of RNA-seq over microarray-based platforms, we demonstrate high reproducibility and comparability. We identify thousands of long non-coding RNAs as potential regulators of pollen development, hundreds of changes in alternative splicing and provide insight into mRNA translation rate and storage in developing pollen. Our analysis delivers an integrated perspective of gene expression dynamics in developing Arabidopsis pollen and a foundation for studying the role of alternative splicing in this model.

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

The Influence of Minor Aortic Branches in Patient-Specific Flow Simulations of Type-B Aortic Dissection - C. Stokes; F. Haupt; D. Becker; V. Muthurangu; H. von Tengg-Kobligk; S. Balabani; V. Díaz-Zuccarini (Annals of Biomedical Engineering, 2023)
Type-B aortic dissection (TBAD) is a disease in which a tear develops in the intimal layer of the descending aorta forming a true lumen and false lumen (FL). Because disease outcomes are thought to be influenced by haemodynamic quantities such as pressure and wall shear stress (WSS), their analysis via numerical simulations may provide valuable clinical insights. Major aortic branches are routinely included in simulations but minor branches are virtually always neglected, despite being implicated in TBAD progression and the development of complications. As minor branches are estimated to carry about 7–21% of cardiac output, neglecting them may affect simulation accuracy. We present the first simulation of TBAD with all pairs of intercostal, subcostal and lumbar arteries, using 4D-flow MRI (4DMR) to inform patient-specific boundary conditions. Compared to an equivalent case without minor branches, their inclusion improved agreement with 4DMR velocities, reduced time-averaged WSS (TAWSS) and transmural pressure and elevated oscillatory shear in regions where FL dilatation and calcification were observed in vivo . Minor branch inclusion resulted in differences of 60-75% in these metrics of potential clinical relevance, indicating a need to account for minor branch flow loss if simulation accuracy is sought.

Genetic characterization of infectious spleen and kidney necrosis virus in Banggai cardinalfish Pterapogon kauderni identified from eight separate cases between 2000 and 2017 - Samantha A. Koda; Kuttichantran Subramaniam; Joseph M. Groff; Roy P. Yanong; Deborah B. Pouder; Matt Pedersen; Craig Pelton; Michael M. Garner; Nicholas B. D. Phelps; Anibal G. Armien; Michael W. Hyatt; Paul M. Hick; et al. (Journal of Fish Diseases, 2023)

TPC1 vacuole SV channel gains further shape – voltage priming of calcium-dependent gating - Rainer Hedrich; Thomas D. Müller; Irene Marten; Dirk Becker (Trends in Plant Science, 2023)

Community recommendations for geochemical data, services and analytical capabilities in the 21st century - Marthe Klöcking; Lesley Wyborn; Kerstin A. Lehnert; Bryant Ware; Alexander M. Prent; Lucia Profeta; Fabian Kohlmann; Wayne Noble; Ian Bruno; Sarah Lambart; Halimulati Ananuer; Nicholas D. Barber; et al. (Geochimica et Cosmochimica Acta, 2023)

Managing for climate resilient fisheries: Applications to the Southern Ocean - Vasco. Chavez-Molina; Emily S. Nocito; Eloise Carr; Rachel D. Cavanagh; Zephyr Sylvester; Sarah L. Becker; Diana D. Dorman; Bryan Wallace; Casey White; Cassandra M. Brooks (Ocean & Coastal Management, 2023)

Improving the haploidization toolbox: Maternal factors take the stage - María Flores-Tornero; Helena Sapeta; Jörg D. Becker (Molecular Plant, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Hydroacoustic surveys reveal the distribution of mid-water fish around two artificial reef designs in temperate Australia - Alistair Becker; Michael B. Lowry; Ashley M. Fowler; Matthew D. Taylor (Fisheries Research, 2023)

Preface: advances in the ecology of shallow lakes - José L. Attayde; Renata Panosso; Vanessa Becker; Juliana D. Dias; Erik Jeppesen (Hydrobiologia, 2022)

Machine learning techniques to characterize functional traits of plankton from image data - Eric C. Orenstein; Sakina‐Dorothée Ayata; Frédéric Maps; Érica C. Becker; Fabio Benedetti; Tristan Biard; Thibault de Garidel‐Thoron; Jeffrey S. Ellen; Filippo Ferrario; Sarah L. C. Giering; Tamar Guy‐Haim; Laura Hoebeke; et al. (Limnology and Oceanography, 2022)
Plankton imaging systems supported by automated classification and analysis have improved ecologists' ability to observe aquatic ecosystems. Today, we are on the cusp of reliably tracking plankton populations with a suite of lab‐based and in situ tools, collecting imaging data at unprecedentedly fine spatial and temporal scales. But these data have potential well beyond examining the abundances of different taxa; the individual images themselves contain a wealth of information on functional traits. Here, we outline traits that could be measured from image data, suggest machine learning and computer vision approaches to extract functional trait information from the images, and discuss promising avenues for novel studies. The approaches we discuss are data agnostic and are broadly applicable to imagery of other aquatic or terrestrial organisms.

Light at night disrupts biological clocks, calendars, and immune function - William H. Walker; Jacob R. Bumgarner; Darius D. Becker-Krail; Laura E. May; Jennifer A. Liu; Randy J. Nelson (Seminars in Immunopathology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Connectivity of Large-Bodied Fish with a Recovering Estuarine Tidal Marsh, Revealed Using an Imaging Sonar - Mark A. Bennett; Alistair Becker; Troy Gaston; Matthew D. Taylor (Estuaries and Coasts, 2021)

Linalool inhibits the angiogenic activity of endothelial cells by downregulating intracellular ATP levels and activating TRPM8 - Vivien Becker; Xin Hui; Lisa Nalbach; Emmanuel Ampofo; Peter Lipp; Michael D. Menger; Matthias W. Laschke; Yuan Gu (Angiogenesis, 2021)
Angiogenesis crucially contributes to various diseases, such as cancer and diabetic retinopathy. Hence, anti-angiogenic therapy is considered as a powerful strategy against these diseases. Previous studies reported that the acyclic monoterpene linalool exhibits anticancer, anti-inflammatory and anti-oxidative activity. However, the effects of linalool on angiogenesis still remain elusive. Therefore, we investigated the action of (3 R )-(−)-linalool, a main enantiomer of linalool, on the angiogenic activity of human dermal microvascular endothelial cells (HDMECs) by a panel of angiogenesis assays. Non-cytotoxic doses of linalool significantly inhibited HDMEC proliferation, migration, tube formation and spheroid sprouting. Linalool also suppressed the vascular sprouting from rat aortic rings. In addition, Matrigel plugs containing linalool exhibited a significantly reduced microvessel density 7 days after implantation into BALB/c mice. Mechanistic analyses revealed that linalool promotes the phosphorylation of extracellular signal-regulated kinase (ERK), downregulates the intracellular level of adenosine triphosphate (ATP) and activates the transient receptor potential cation channel subfamily M (melastatin) member (TRPM)8 in HDMECs. Inhibition of ERK signaling, supplementation of ATP and blockade of TRPM8 significantly counteracted linalool-suppressed HDMEC spheroid sprouting. Moreover, ATP supplementation completely reversed linalool-induced ERK phosphorylation. In addition, linalool-induced ERK phosphorylation inhibited the expression of bone morphogenetic protein (BMP)-2 and linalool-induced TRPM8 activation caused the inhibition of β1 integrin/focal adhesion kinase (FAK) signaling. These findings indicate an anti-angiogenic effect of linalool, which is mediated by downregulating intracellular ATP levels and activating TRPM8.

Chemical and toxicological evaluation along with unprecedented transformation products during photolysis and heterogeneous photocatalysis of chloramphenicol in different aqueous matrices - Eduardo O. Marson; Cleiseano E.S. Paniagua; Nayara M. Costa-Serge; Raquel M.F. Sousa; Gizele D. Silva; Raquel W. Becker; Carla Sirtori; Maria Clara V. M. Starling; Solidônio R. Carvalho; Alam G. Trovó (Environmental Science and Pollution Research, 2021)

Longitudinal uncoupling of the heart and arteries with aging in a community-dwelling population - Majd AlGhatrif; Chris H. Morrell; Lewis C. Becker; Paul D. Chantler; Samer S. Najjar; Luigi Ferrucci; Gary Gerstenblith; Edward G. Lakatta (GeroScience, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Temporal variability in size and growth of Atlantic herring in the Gulf of Maine - James R. Becker; Matthew D. Cieri; David A. Libby; Adam St. Gelais; Graham Sherwood; Yong Chen (Journal of Fish Biology, 2020)
Variability in life history traits and structural diversity of commercially exploited fishes in response to stress can impact their population dynamics and sustainability. Using data from a fishery dependent sampling program from 1978 to 2011, we evaluated temporal variability of size and growth of adult Atlantic herring ( Clupea harengus ) in the Gulf of Maine. We then developed and tested the hypotheses on the links of such temporal changes to population density and environmental factors and found decreases in size and growth potential. Generalized additive models found that density dependence was the main driver of such changes over sea surface temperature and salinity. Our results highlight the importance of density dependent processes in regulating growth and population size structure for Atlantic herring in the Gulf of Maine.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Reactive navigation system based on H∞ control system and LiDAR readings on corn crops - A. E. B. Velasquez; V. A. H. Higuti; H. B. Guerrero; M. V. Gasparino; D. V. Magalhães; R. V. Aroca; M. Becker (Precision Agriculture, 2020)

Ecological and evolutionary drivers of haemoplasma infection and bacterial genotype sharing in a Neotropical bat community - Daniel J. Becker; Kelly A. Speer; Alexis M. Brown; M. Brock Fenton; Alex D. Washburne; Sonia Altizer; Daniel G. Streicker; Raina K. Plowright; Vladimir E. Chizhikov; Nancy B. Simmons; Dmitriy V. Volokhov (Molecular Ecology, 2020)
Most emerging pathogens can infect multiple species, underlining the importance of understanding the ecological and evolutionary factors that allow some hosts to harbour greater infection prevalence and share pathogens with other species. However, our understanding of pathogen jumps is based primarily around viruses, despite bacteria accounting for the greatest proportion of zoonoses. Because bacterial pathogens in bats (order Chiroptera) can have conservation and human health consequences, studies that examine the ecological and evolutionary drivers of bacterial prevalence and barriers to pathogen sharing are crucially needed. Here were studied haemotropic Mycoplasma spp. (i.e., haemoplasmas) across a species‐rich bat community in Belize over two years. Across 469 bats spanning 33 species, half of individuals and two‐thirds of species were haemoplasma positive. Infection prevalence was higher for males and for species with larger body mass and colony sizes. Haemoplasmas displayed high genetic diversity (21 novel genotypes) and strong host specificity. Evolutionary patterns supported codivergence of bats and bacterial genotypes alongside phylogenetically constrained host shifts. Bat species centrality to the network of shared haemoplasma genotypes was phylogenetically clustered and unrelated to prevalence, further suggesting rare—but detectable—bacterial sharing between species. Our study highlights the importance of using fine phylogenetic scales when assessing host specificity and suggests phylogenetic similarity may play a key role in host shifts not only for viruses but also for bacteria. Such work more broadly contributes to increasing efforts to understand cross‐species transmission and the epidemiological consequences of bacterial pathogens.

More reliable coastal SST forecasts from the North American multimodel ensemble - G. Hervieux; M. A. Alexander; C. A. Stock; M. G. Jacox; K. Pegion; E. Becker; F. Castruccio; D. Tommasi (Climate Dynamics, 2019)

Nerve/glial antigen 2 is crucially involved in the revascularization of freely transplanted pancreatic islets - Lisa Nalbach; Beate M. Schmitt; Vivien Becker; Anja Scheller; Matthias W. Laschke; Michael D. Menger; Emmanuel Ampofo (Cell and Tissue Research, 2019)

Constraining the Oceanic Uptake and Fluxes of Greenhouse Gases by Building an Ocean Network of Certified Stations: The Ocean Component of the Integrated Carbon Observation System, ICOS-Oceans - Tobias Steinhoff; Thanos Gkritzalis; Siv K. Lauvset; Steve Jones; Ute Schuster; Are Olsen; Meike Becker; Roberto Bozzano; Fabio Brunetti; Carolina Cantoni; Vanessa Cardin; Denis Diverrès; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Correction to: Human–Nature Relationships and Normative Beliefs Influence Behaviors that Reduce the Spread of Aquatic Invasive Species - Carena J. van Riper; Matthew H. E. M. Browning; Douglas Becker; William Stewart; Cory D. Suski; Lara Browning; Elizabeth Golebie (Environmental Management, 2019)

Antipredator response diminishes during periods of resource deficit for a large herbivore - B. A. Oates; J. A. Merkle; M. J. Kauffman; S. R. Dewey; M. D. Jimenez; J. M. Vartanian; S. A. Becker; J. R. Goheen (Ecology, 2019)
The starvation–predation hypothesis predicts that, during resource shortages, prey forego antipredator behavior and forage as much as possible to avoid starvation, even when risk of predation is high. We tested this hypothesis using GPS locations collected simultaneously from moose ( Alces alces ) and wolves ( Canis lupus ) in the Greater Yellowstone Ecosystem of North America. We assessed shifts in the speed, displacement, and habitat selection of moose 24 h following encounter with wolves (0–1,500 m distance). We examined whether the strength of antipredator behaviors would weaken as winter progressed and the nutritional condition of moose declined. Moose responded to wolf encounters by increasing their rate of movement in early winter, but only within 500 m distance. Importantly, these responses attenuated as winter progressed. Moose did not avoid their preferred foraging habitat (riparian areas) following encounters with wolves at any distance, and instead they more strongly selected riparian areas, especially in early winter. Our findings support theoretical predictions that resource deficits should dampen prey antipredator behavior, and suggest that nutritional condition of prey may buffer against run‐away risk effects in food webs involving large mammalian predators and prey.

Transcriptomics of Arabidopsis sperm cells at single-cell resolution - Chandra Shekhar Misra; Mário R. Santos; Mariana Rafael-Fernandes; Nuno P. Martins; Marta Monteiro; Jörg D. Becker (Plant Reproduction, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Molecular detection of Mycoplasma ovis in an outbreak of hemolytic anemia in sheep from Veracruz, Mexico - J. M. Martínez-Hernández; G. G. Ballados-González; D. Fernández-Bandala; S. Martínez-Soto; V. Velázquez-Osorio; P. B. Martínez-Rodríguez; A. Cruz-Romero; E. Grostieta; Y. Lozano-Sardaneta; P. Colunga Salas; I. Becker; S. Sánchez-Montes (Tropical Animal Health and Production, 2019)

Grain yield, evapotranspiration, and water-use efficiency of maize hybrids differing in drought tolerance - Baozhen Hao; Qingwu Xue; Thomas H. Marek; Kirk E. Jessup; Jacob D. Becker; Xiaobo Hou; Wenwei Xu; Edsel D. Bynum; Brent W. Bean; Paul D. Colaizzi; Terry A. Howell (Irrigation Science, 2019)

Prospective study of serum and ionized magnesium pharmacokinetics in the treatment of children with severe acute asthma - Sarah M. Becker; Kathleen M. Job; Kelly Lima; Ty J. Forbes; Jadon Wagstaff; Nam K. Tran; Catherine M. Sherwin; Douglas S. Nelson; Michael D. Johnson; Joseph E. Rower (European Journal of Clinical Pharmacology, 2019)

Human-Nature Relationships and Normative Beliefs Influence Behaviors that Reduce the Spread of Aquatic Invasive Species - Carena J. van Riper; Matthew H. E. M. Browning; Douglas Becker; William Stewart; Cory D. Suski; Lara Browning; Elizabeth Golebie (Environmental Management, 2019)

Late Holocene palynology of a saline lake in the Pantanal of Nhecolândia, Brazil - B.F. Becker; S.A.F. da Silva-Caminha; R.L. Guerreiro; E.J. de Oliveira; C. D'Apolito; M.L. Assine (Palynology, 2018)

Investigating the Functional Role of an Artificial Reef Within an Estuarine Seascape: a Case Study of Yellowfin Bream (Acanthopagrus australis) - Matthew D. Taylor; Alistair Becker; Michael B. Lowry (Estuaries and Coasts, 2018)

Comparative analysis of transcriptomic responses to sub-lethal levels of six environmentally relevant pesticides in Saccharomyces cerevisiae - Fátima N. Gil; Alina C. Gonçalves; Jörg D. Becker; Cristina A. Viegas (Ecotoxicology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Managing the development of artificial reef systems: The need for quantitative goals - Alistair Becker; Matthew D. Taylor; Heath Folpp; Michael B. Lowry (Fish and Fisheries, 2018)
Fisheries enhancement initiatives are a potentially useful tool for managers to supplement traditional approaches. Habitat‐based enhancements often deploy artificial reefs with the aim to increase the available structure to augment local production, yet current assessment approaches make it difficult to assess whether these reefs achieve pre‐deployment goals. This makes it hard for managers to determine whether artificial reefs could improve their fishery outputs, potentially leading to missed opportunities and reduced production. We reviewed 270 research articles to determine whether existing monitoring studies identify whether artificial reefs meet their pre‐deployment goals, thereby providing some evidence of their suitability for certain fisheries. We found only 62% of these studies clearly articulated the original goals of the reef. Goals were qualitative, and most studies were conducted over insufficient time frames to allow for ecological communities to stabilize and mature. It is therefore difficult to determine the success or failure of many artificial reefs in addressing the management issues for which they were deployed. In the light of these findings, we think the setting of explicit quantitative goals (which may be biological, social or economic), and monitoring the performance of reefs against these goals, could stimulate the broader application of artificial reefs in fisheries management strategies. Such an approach has been successfully adopted in aquaculture‐based fisheries enhancement, and we explain how current evaluation methods such as harvest strategies can be easily adapted to quantitatively monitor artificial reef performance.

A Belgian consensus protocol for autologous hematopoietic stem cell transplantation in multiple sclerosis - Guy Laureys; Barbara Willekens; Ludo Vanopdenbosch; Olivier Deryck; Dominik Selleslag; Miguel D’Haeseleer; Ann De Becker; Bénédicte Dubois; Daan Dierickx; Gaetano Perrotta; Virginie De Wilde; Vincent van Pesch; et al. (Acta Neurologica Belgica, 2018)

Direct and Indirect Interactions Between Lower Estuarine Mangrove and Saltmarsh Habitats and a Commercially Important Penaeid Shrimp - Matthew D. Taylor; Alistair Becker; Natalie A. Moltschaniwskyj; Troy F. Gaston (Estuaries and Coasts, 2018)

Response of estuarine consumer communities following the stocking of a juvenile penaeid ( Penaeus plebejus ) over two consecutive years - A. Becker; M. B. Lowry; M. D. Taylor (Fisheries Management and Ecology, 2018)
Research programmes that monitor and evaluate the impact of stocking activities are essential to quantify effects of stocking and provide information for adaptive management of future releases. The consumer communities in two estuaries stocked with 5.8 million post‐larvae eastern king prawn Penaeus plebejus (Hess) were monitored, both before and after stocking, and relative to two similar reference estuaries. Following stocking, there was evidence of increases in the abundances of prawns within stocked estuaries. Communities in all four estuaries showed significant levels of variation over time as well as among the systems themselves. Changes in overall diversity were similarly observed. The presence or absence of vegetation and other seasonal effects were found to explain most of the observed variation in the community assemblage, while prawn stocking appeared to have a little detectable influence. While this study points to minimal impacts of prawn stocking on the consumer community at the densities used, research into potential shifts in resource use by competitors and the growth and survival of prawns is required to fully understand post‐release changes in stocked systems.

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Rapid salinity changes affect the survival and physiology of a penaeid prawn: Implications of flood events on recruitment to the fishery - K. J. Tyler; A. Becker; N. A. Moltschaniwskyj; M. D. Taylor (Fisheries Management and Ecology, 2017)
Estuaries act as nurseries for many penaeid prawns, but these habitats are highly susceptible to salinity decline through flooding. The rate of salinity decline and duration of exposure to non‐optimal salinity may affect survival and subsequent recruitment of prawns to the fishery. This study aimed to determine the effect of salinity fluctuations observed in local estuaries during flood events using a novel dilution approach. Mortality of juvenile Melicertus plebejus (Hess) was assessed after 24 hr exposure to 24 rates of salinity decline ranging from 0.01% to 20% per hr. After the salinity decline, prawns were held at the final salinities for five days before again assessing mortality as well as aerobic metabolic rate and prawn water content. Salinity decline from 36 to ~0.8 led to 50% mortality, but continued exposure to low salinity for five days increased mortality at this salinity to 99% and shifted the 50% mortality point to salinity ~5. Aerobic metabolic rate and water content data suggested the cause of mortality due to exposure to salinities

The Geoid Slope Validation Survey 2014 and GRAV-D airborne gravity enhanced geoid comparison results in Iowa - Y. M. Wang; C. Becker; G. Mader; D. Martin; X. Li; T. Jiang; S. Breidenbach; C. Geoghegan; D. Winester; S. Guillaume; B. Bürki (Journal of Geodesy, 2017)

Intercomparison of Approaches to the Empirical Line Method for Vicarious Hyperspectral Reflectance Calibration - Joseph D. Ortiz; Dulcinea Avouris; Stephen Schiller; Jeffrey C. Luvall; John D. Lekki; Roger P. Tokars; Robert C. Anderson; Robert Shuchman; Michael Sayers; Richard Becker (Frontiers in Marine Science, 2017)

Adaptive threat management framework: integrating people and turtles - Valéria R. F. da Silva; Sylvia F. Mitraud; Maria L. C. P. Ferraz; Eduardo H. S. M. Lima; Maria Thereza D. Melo; Armando J. B. Santos; Augusto César C. D. da Silva; Jaqueline C. de Castilhos; Jamyle A. F. Batista; Gustave G. Lopez; Frederico Tognin; João Carlos Thomé; et al. (Environment, Development and Sustainability, 2016)

Tidal amplitude and fish abundance in the mouth region of a small estuary - A. Becker; A. K. Whitfield; P. D. Cowley; V. J. Cole; M. D. Taylor (Journal of Fish Biology, 2016)
Using an acoustic underwater camera (Dual Frequency IDentification SONar , DIDSON ), the abundance and direction of movement of fishes > 80 mm total length ( L T ) in the mouth of a small South African estuary during spring and neap tidal cycles were observed. While the sizes of fishes recorded were consistent across both tide cycles, the number of fishes passing the camera was significantly greater during the smaller neap tides. Schooling behaviour was more pronounced for fishes that were travelling into the estuary compared to fishes swimming towards the ocean.

Efficacy assessment of three inactivated koi herpes virus antigen preparations against experimental challenge virus infection in common carp - T Schmid; L Gaede; K Böttcher; G Bräuer; D Fichtner; R Beckmann; S Speck; F Becker; U Truyen (Journal of Fish Diseases, 2016)

Root traits contributing to drought tolerance of synthetic hexaploid wheat in a greenhouse study - Steven R. Becker; Patrick F. Byrne; Scott D. Reid; William L. Bauerle; John K. McKay; Scott D. Haley (Euphytica, 2016)

A Comparison of Seismicity Characteristics and Fault Structure Between Stick–Slip Experiments and Nature - T. H. W. Goebel; C. G. Sammis; T. W. Becker; G. Dresen; D. Schorlemmer (Pure and Applied Geophysics, 2015)

The effects of self-control on cognitive resource allocation during sustained attention: a transcranial Doppler investigation - Alexandra Becker; Arielle R. Mandell; June P. Tangney; Linda D. Chrosniak; Tyler H. Shaw (Experimental Brain Research, 2015)

DNA barcoding and morphological identification of neotropical ichthyoplankton from the Upper Paraná and São Francisco - R. A. Becker; N. G. Sales; G. M. Santos; G. B. Santos; D. C. Carvalho (Journal of Fish Biology, 2015)
The identification of fish larvae from two neotropical hydrographic basins using traditional morphological taxonomy and DNA barcoding revealed no conflicting results between the morphological and barcode identification of larvae. A lower rate (25%) of correct morphological identification of eggs as belonging to migratory or non‐migratory species was achieved. Accurate identification of ichthyoplankton by DNA barcoding is an important tool for fish reproductive behaviour studies, correct estimation of biodiversity by detecting eggs from rare species, as well as defining environmental and management strategies for fish conservation in the neotropics.

Acid sphingomyelinase inhibition protects mice from lung edema and lethal Staphylococcus aureus sepsis - Huiming Peng; Cao Li; Stephanie Kadow; Brian D. Henry; Jörg Steinmann; Katrin Anne Becker; Andrea Riehle; Natalie Beckmann; Barbara Wilker; Pin-Lan Li; Timothy Pritts; Michael J. Edwards; et al. (Journal of Molecular Medicine, 2015)

Mapping global cropland and field size - Steffen Fritz; Linda See; Ian McCallum; Liangzhi You; Andriy Bun; Elena Moltchanova; Martina Duerauer; Fransizka Albrecht; Christian Schill; Christoph Perger; Petr Havlik; Aline Mosnier; et al. (Global Change Biology, 2015)
A new 1 km global IIASA ‐ IFPRI cropland percentage map for the baseline year 2005 has been developed which integrates a number of individual cropland maps at global to regional to national scales. The individual map products include existing global land cover maps such as GlobCover 2005 and MODIS v.5, regional maps such as AFRICOVER and national maps from mapping agencies and other organizations. The different products are ranked at the national level using crowdsourced data from Geo‐Wiki to create a map that reflects the likelihood of cropland. Calibration with national and subnational crop statistics was then undertaken to distribute the cropland within each country and subnational unit. The new IIASA ‐ IFPRI cropland product has been validated using very high‐resolution satellite imagery via Geo‐Wiki and has an overall accuracy of 82.4%. It has also been compared with the EarthStat cropland product and shows a lower root mean square error on an independent data set collected from Geo‐Wiki. The first ever global field size map was produced at the same resolution as the IIASA ‐ IFPRI cropland map based on interpolation of field size data collected via a Geo‐Wiki crowdsourcing campaign. A validation exercise of the global field size map revealed satisfactory agreement with control data, particularly given the relatively modest size of the field size data set used to create the map. Both are critical inputs to global agricultural monitoring in the frame of GEOGLAM and will serve the global land modelling and integrated assessment community, in particular for improving land use models that require baseline cropland information. These products are freely available for downloading from the http://cropland.geo-wiki.org website.

Generation of Mice Lacking DUF1220 Protein Domains: Effects on Fecundity and Hyperactivity - J. G. Keeney; M. S. O’Bleness; N. Anderson; J. M. Davis; N. Arevalo; N. Busquet; W. Chick; J. Rozman; S. M. Hölter; L. Garrett; M. Horsch; J. Beckers; et al. (Mammalian Genome, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Differential transcriptomic responses of ancient and modern Daphnia genotypes to phosphorus supply - Priyanka Roy Chowdhury; Dagmar Frisch; Dörthe Becker; Jacqueline A. Lopez; Lawrence J. Weider; John K. Colbourne; Punidan D. Jeyasingh (Molecular Ecology, 2015)
Little is known about the role of transcriptomic changes in driving phenotypic evolution in natural populations, particularly in response to anthropogenic environmental change. Previous analyses of Daphnia genotypes separated by centuries of evolution in a lake using methods in resurrection ecology revealed striking genetic and phenotypic shifts that were highly correlated with anthropogenic environmental change, specifically phosphorus (P)‐driven nutrient enrichment (i.e. eutrophication). Here, we compared the transcriptomes of two ancient (~700‐year‐old) and two modern (~10‐year‐old) genotypes in historic (low P) and contemporary (high P) environmental conditions using microarrays. We found considerable transcriptomic variation between ‘ancient’ and ‘modern’ genotypes in both treatments, with stressful (low P) conditions eliciting differential expression ( DE ) of a larger number of genes. Further, more genes were DE between ‘ancient’ and ‘modern’ genotypes than within these groups. Expression patterns of individual genes differed greatly among genotypes, suggesting that different transcriptomic responses can result in similar phenotypes. While this confounded patterns between ‘ancient’ and ‘modern’ genotypes at the gene level, patterns were discernible at the functional level: annotation of DE genes revealed particular enrichment of genes involved in metabolic pathways in response to P‐treatments. Analyses of gene families suggested significant DE in pathways already known to be important in dealing with P‐limitation in Daphnia as well as in other organisms. Such observations on genotypes of a single natural population, separated by hundreds of years of evolution in contrasting environmental conditions before and during anthropogenic environmental changes, highlight the important role of transcriptional mechanisms in the evolutionary responses of populations.

A Tailored Computation of the Mean Dynamic Topography for a Consistent Integration into Ocean Circulation Models - S. Becker; M. Losch; J. M. Brockmann; G. Freiwald; W.-D. Schuh (Surveys in Geophysics, 2014)

Comparative fitness of Alternaria species causing leaf blotch and fruit spot of apple in Australia - D. O. C. Harteveld; O. A. Akinsanmi; M. F. Becker; A. Drenth (Australasian Plant Pathology, 2014)

Ept7 influences estrogen action in the pituitary gland and body weight of rats - Scott G. Kurz; Kirsten L. Dennison; Nyssa Becker Samanas; Maureen Peters Hickman; Quincy A. Eckert; Tiffany L. Walker; Andrea S. Cupp; James D. Shull (Mammalian Genome, 2014)

Heat and water stress induce unique transcriptional signatures of heat-shock proteins and transcription factors in grapevine - Margarida Rocheta; Jörg D. Becker; João L. Coito; Luísa Carvalho; Sara Amâncio (Functional & Integrative Genomics, 2014)

Differential nitric oxide synthesis and host apoptotic events correlate with bleaching susceptibility in reef corals - T. D. Hawkins; T. Krueger; S. Becker; P. L. Fisher; S. K. Davy (Coral Reefs, 2014)

Long‐term endemism of two highly divergent lineages of the amphibian‐killing fungus in the A tlantic F orest of B razil - D. Rodriguez; C. G. Becker; N. C. Pupin; C. F. B. Haddad; K. R. Zamudio (Molecular Ecology, 2014)
The recent global spread of the amphibian‐killing fungus [ B atrachochytrium dendrobatidis ( Bd )] has been closely tied to anthropogenic activities; however, regional patterns of spread are not completely understood. Using historical samples, we can test whether B d was a spreading or endemic pathogen in a region within a particular time frame, because those two disease states provide different predictions for the regional demographic dynamics and population genetics of B d . Testing historical patterns of pathogen prevalence and population genetics under these predictions is key to understanding the evolution and origin of B d . Focusing on the A tlantic F orest ( AF ) of B razil, we used q PCR assays to determine the presence or absence of B d on 2799 preserved postmetamorphic anurans collected between 1894 and 2010 and used semi‐nested PCR s to determine the frequency of r RNA ITS 1 haplotypes from 52 samples. Our earliest date of detection was 1894. A mean prevalence of 23.9% over time and spatiotemporal patterns of B d clusters indicate that B d has been enzootic in the B razilian AF with no evidence of regional spread within the last 116 years. ITS 1 haplotypes confirm the long‐term presence of two divergent strains of B d ( B d GPL and B d‐Brazil ) and three spatiotemporally broad genetic demes within B d GPL , indicating that B d was not introduced into southeast B razil by the bullfrog trade. Our data show that the evolutionary history and pathogen dynamics of B d in B razil is better explained by the endemic pathogen hypothesis.

Sun Safety Among Farmers and Farmworkers: A Review - Gregory D. Kearney; Xiaohui Xu; Jo Anne G. Balanay; Alan J. Becker (Journal of Agromedicine, 2014)

Inhibition of cardiac Kv1.5 and Kv4.3 potassium channels by the class Ia anti-arrhythmic ajmaline: mode of action - F. Fischer; N. Vonderlin; E. Zitron; C. Seyler; D. Scherer; R. Becker; H. A. Katus; E. P. Scholz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Foreleg Ornaments Do Not Hinder Foraging Success in Brush-Legged Wolf Spiders - Mari F. Pesek; Eileen A. Hebets; Laura Sullivan-Beckers; Kasey D. Fowler-Finn (Journal of Insect Behavior, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

A Novel Human Glycoprotein ACA is an Upstream Regulator of Human Hematopoiesis - Z. A. Becker-Kojić; J. R. Ureña-Peralta; R. Saffrich; F. J. Rodriguez-Jiménez; M. P. Rubio; P. Rios; A. Romero; A. D. Ho; M. Stojković (Bulletin of Experimental Biology and Medicine, 2013)

Vascular endothelial growth factor C is increased in endometrium and promotes endothelial functions, vascular permeability and angiogenesis and growth of endometriosis - Hui Xu; Tao Zhang; Gene Chi Wai Man; Katie E. May; Christian M. Becker; Tina N. Davis; Andrew L. Kung; Amy E. Birsner; Robert J. D’Amato; Alice Wai Yee Wong; Chi Chiu Wang (Angiogenesis, 2013)

Recommendation for the discrimination of human-related and natural seismicity - T. Dahm; D. Becker; M. Bischoff; S. Cesca; B. Dost; R. Fritschen; S. Hainzl; C. D. Klose; D. Kühn; S. Lasocki; Th. Meier; M. Ohrnberger; et al. (Journal of Seismology, 2013)

Smoking, variation in N-acetyltransferase 1 (NAT1) and 2 (NAT2), and risk of non-Hodgkin lymphoma: a pooled analysis within the InterLymph consortium - Todd M. Gibson; Karin E. Smedby; Christine F. Skibola; David W. Hein; Susan L. Slager; Silvia de Sanjosé; Claire M. Vajdic; Yawei Zhang; Brian C.-H. Chiu; Sophia S. Wang; Henrik Hjalgrim; Alexandra Nieters; et al. (Cancer Causes & Control, 2013)

Cyclophosphamide promotes engraftment of gene-modified cells in a mouse model of Fanconi anemia without causing cytogenetic abnormalities - Jennifer E. Adair; Xin Zhao; Sylvia Chien; Min Fang; Martin E. Wohlfahrt; Grant D. Trobridge; Jason A. Taylor; Brian C. Beard; Hans-Peter Kiem; Pamela S. Becker (Journal of Molecular Medicine, 2012)

Molecular fingerprinting of Staphylococcus aureus isolated from patients with osteomyelitis in Argentina and clonal distribution of the cap5(8) genes and of other selected virulence genes - S. M. Lattar; L. P. N. Tuchscherr; D. Centrón; K. Becker; S. C. Predari; F. R. Buzzola; D. A. Robinson; D. O. Sordelli (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Ion levels in the gastrointestinal tract content of freshwater and marine–estuarine teleosts - Alexssandro G. Becker; Jamile F. Gonçalves; Marcelo D. M. Burns; João Paes Vieira; João Radünz Neto; Bernardo Baldisserotto (Fish Physiology and Biochemistry, 2012)

Mesenchymal stromal cells (MSCs): science and f(r)iction - Karen Bieback; Patrick Wuchter; Daniel Besser; Werner Franke; Matthias Becker; Michael Ott; Martin Pacher; Nan Ma; Christof Stamm; Harald Klüter; Albrecht Müller; Anthony D. Ho (Journal of Molecular Medicine, 2012)

ENSURF: multi-model sea level forecast – implementation and validation results for the IBIROOS and Western Mediterranean regions - B. Pérez; R. Brouwer; J. Beckers; D. Paradis; C. Balseiro; K. Lyons; M. Cure; M. G. Sotillo; B. Hackett; M. Verlaan; E. A. Fanjul (Ocean Science, 2012)
ENSURF (Ensemble SURge Forecast) is a multi-model application for sea level forecast that makes use of several storm surge or circulation models and near-real time tide gauge data in the region, with the following main goals: 1. providing easy access to existing forecasts, as well as to its performance and model validation, by means of an adequate visualization tool; 2. generation of better forecasts of sea level, including confidence intervals, by means of the Bayesian Model Average technique (BMA). The Bayesian Model Average technique generates an overall forecast probability density function (PDF) by making a weighted average of the individual forecasts PDF's; the weights represent the Bayesian likelihood that a model will give the correct forecast and are continuously updated based on the performance of the models during a recent training period. This implies the technique needs the availability of sea level data from tide gauges in near-real time. The system was implemented for the European Atlantic facade (IBIROOS region) and Western Mediterranean coast based on the MATROOS visualization tool developed by Deltares. Results of validation of the different models and BMA implementation for the main harbours are presented for these regions where this kind of activity is performed for the first time. The system is currently operational at Puertos del Estado and has proved to be useful in the detection of calibration problems in some of the circulation models, in the identification of the systematic differences between baroclinic and barotropic models for sea level forecasts and to demonstrate the feasibility of providing an overall probabilistic forecast, based on the BMA method.

Chronic hyperhomocysteinemia induces oxidative damage in the rat lung - Aline A. da Cunha; Andréa G. K. Ferreira; Maira J. da Cunha; Carolina D. Pederzolli; Débora L. Becker; Juliana G. Coelho; Carlos S. Dutra-Filho; Angela T. S. Wyse (Molecular and Cellular Biochemistry, 2011)

Expression of immune relevant genes in pigs under the influence of low doses of deoxynivalenol (DON) - Christiane Becker; Martina Reiter; Michael W. Pfaffl; Heinrich H. D. Meyer; Johann Bauer; Karsten H. D. Meyer (Mycotoxin Research, 2011)

Platelet decline as a predictor of brain injury in HIV infection - Ann B. Ragin; Gypsyamber D’Souza; Sandra Reynolds; Eric Miller; Ned Sacktor; Ola A. Selnes; Eileen Martin; Barbara R. Visscher; James T. Becker (Journal of NeuroVirology, 2011)

Data Interpolating Empirical Orthogonal Functions (DINEOF): a tool for geophysical data analyses - A. ALVERA-AZCÁRATE; A. BARTH; D. SIRJACOBS; F. LENARTZ; J. M. BECKERS (Mediterranean Marine Science, 2011)
no abstract

Seismicity at the convergent plate boundary offshore Crete, Greece, observed by an amphibian network - D. Becker; T. Meier; M. Bohnhoff; H.-P. Harjes (Journal of Seismology, 2010)

Validation of extraction methods for total RNA and miRNA from bovine blood prior to quantitative gene expression analyses - Andrea Hammerle-Fickinger; Irmgard Riedmaier; Christiane Becker; Heinrich H. D. Meyer; Michael W. Pfaffl; Susanne E. Ulbrich (Biotechnology Letters, 2010)

Global Bathymetry and Elevation Data at 30 Arc Seconds Resolution: SRTM30_PLUS - J. J. Becker; D. T. Sandwell; W. H. F. Smith; J. Braud; B. Binder; J. Depner; D. Fabre; J. Factor; S. Ingalls; S-H. Kim; R. Ladner; K. Marks; et al. (Marine Geodesy, 2009)

Enhancing temporal correlations in EOF expansions for the reconstruction of missing data using DINEOF - A. Alvera-Azcárate; A. Barth; D. Sirjacobs; J.-M. Beckers (Ocean Science, 2009)
DINEOF (Data Interpolating Empirical Orthogonal Functions) is an EOF-based technique for the reconstruction of missing data in geophysical fields, such as those produced by clouds in sea surface temperature satellite images. A technique to reduce spurious time variability in DINEOF reconstructions is presented. The reconstruction of these images within a long time series using DINEOF can lead to large discontinuities in the reconstruction. Filtering the temporal covariance matrix allows to reduce this spurious variability and therefore more realistic reconstructions are obtained. The approach is tested in a three years sea surface temperature data set over the Black Sea. The effect of the filter in the temporal EOFs is presented, as well as some examples of the improvement achieved with the filtering in the SST reconstruction, both compared to the DINEOF approach without filtering.

Cadmium-induced oxidative stress in two potato cultivars - J. F. Gonçalves; L. A. Tabaldi; D. Cargnelutti; L. B. Pereira; J. Maldaner; A. G. Becker; L. V. Rossato; R. Rauber; M. D. Bagatini; D. A. Bisognin; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2009)

Leaf abundance and phenolic concentrations codetermine the selection of case-building materials by Phylloicus sp. (Trichoptera, Calamoceratidae) - Marcelo S. Moretti; Rafael D. Loyola; Bárbara Becker; Marcos Callisto (Hydrobiologia, 2009)

Biological responses to sediment remediation based on thin layer placement near a former pulp mill in Ward Cove, AK (USA) - D. Scott Becker; Jane E. Sexton; Lucinda A. Jacobs; Barry Hogarty; Karen Keeley (Environmental Monitoring and Assessment, 2009)

Analyses of associations with asthma in four asthma population samples from Canada and Australia - Denise Daley; Mathieu Lemire; Loubna Akhabir; Moira Chan-Yeung; Jian Qing He; Treena McDonald; Andrew Sandford; Dorota Stefanowicz; Ben Tripp; David Zamar; Yohan Bosse; Vincent Ferretti; et al. (Human Genetics, 2009)

Further development of bithionol therapy as a treatment for amoebic gill disease in Atlantic salmon, Salmo salar L. - R L Florent; J Becker; M D Powell (Journal of Fish Diseases, 2009)
This study examined the efficacy of bithionol as a prophylactic or therapeutic oral treatment for Atlantic salmon (AS), Salmo salar , affected by amoebic gill disease (AGD). Furthermore, it explored the interaction of bithionol oral therapy with the current standard treatment (a freshwater bath for at least 3 h). The efficacy of three medicated feeds was determined in the trial by feeding AGD‐affected AS at 1% body weight (BW) day −1 either oil coated commercial feed (control) or prophylactic and therapeutic bithionol at 25 mg kg −1 feed. Feeding commenced 2 weeks prior to exposure to Neoparamoeba spp. at 300 cells L −1 and continued for 49 days post‐exposure (PE). Bithionol when fed as a 2‐week prophylactic or therapeutic treatment at 25 mg kg −1 feed delayed the onset of AGD pathology and reduced the percentage of gill filaments with lesions. Administration of a 3‐h freshwater bath at 28 days PE significantly reduced amoeba numbers to a similar level across all treatments; in contrast, gross gill score and percent lesioned filaments were reduced to different extents, the control having a significantly higher score than both bithionol treatments. Following the freshwater bath, clinical signs of AGD increased at a similar level across all treatments, albeit controls were significantly higher than the bithionol treatments immediately following freshwater treatment. This study demonstrated that bithionol at 25 mg kg −1 feed, when fed as a 2‐week prophylactic or a therapeutic treatment, delayed and reduced the intensity of AGD pathology and warrants further investigation as a treatment for AGD‐affected AS.

Cuticular wax composition in Cocos nucifera L.: physicochemical analysis of wax components and mapping of their QTLs onto the coconut molecular linkage map - M. Riedel; M. Riederer; D. Becker; A. Herran; A. Kullaya; G. Arana-López; L. Peña-Rodríguez; N. Billotte; V. Sniady; W. Rohde; E. Ritter (Tree Genetics & Genomes, 2009)

Repeated cycles of chronic intermittent ethanol exposure in mice increases voluntary ethanol drinking and ethanol concentrations in the nucleus accumbens - William C. Griffin; Marcelo F. Lopez; Amy B. Yanke; Lawrence D. Middaugh; Howard C. Becker (Psychopharmacology, 2009)

Eye–head coordination in moderately affected Huntington’s Disease patients: do head movements facilitate gaze shifts? - W. Becker; R. Jürgens; J. Kassubek; D. Ecker; B. Kramer; B. Landwehrmeyer (Experimental Brain Research, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Direct reaction of oximes with crotylsarin, cyclosarin, or VX in vitro - G. Becker; A. Kawan; D. Gutzeit; F. Worek; L. Szinicz (Archives of Toxicology, 2007)

Das Großraum-Grundwassermodell Rurscholle - D. Bachmann; B. Becker; A. van Linn; J. Köngeter (Grundwasser, 2007)

Ecological impacts on the limpet Lottia gigantea populations: human pressure over a broad scale on island and mainland intertidal zones - Raphael D. Sagarin; Richard F. Ambrose; Bonnie J. Becker; John M. Engle; Janine Kido; Steven F. Lee; C. Melissa Miner; Steven N. Murray; Peter T. Raimondi; Dan Richards; Christy Roe (Marine Biology, 2007)

BOLITA, an Arabidopsis AP2/ERF-like transcription factor that affects cell expansion and proliferation/differentiation pathways - Nayelli Marsch-Martinez; Raffaella Greco; Jörg D. Becker; Shital Dixit; Jan H. W. Bergervoet; Aarati Karaba; Stefan de Folter; Andy Pereira (Plant Molecular Biology, 2006)

Whole body net ion fluxes, plasma electrolyte concentrations and haematology during a Loma salmonae infection in juvenile rainbow trout, Oncorhynchus mykiss (Walbaum) - M D Powell; D J Speare; J A Becker (Journal of Fish Diseases, 2006)
Loma salmonae infections of salmonids culminate in the development of branchial xenomas and subsequent focal hyperplasia of the lamellar or filament epithelium following xenoma rupture and spore release. The effects of this acute branchial disruption upon net ionic flux rates and plasma electrolyte concentrations were determined in juvenile rainbow trout given an experimental oral exposure to L. salmonae . Mean numbers of branchial xenomas peaked at week 5 post‐exposure (PE), which coincided with a reduction in the specific growth rate, although there were no significant differences in mass, length or condition of Loma ‐exposed fish compared with unexposed controls. Following exposure, negative net whole body Na + and K + fluxes decreased, whereas net Cl − fluxes remained unchanged compared with non‐exposed control fish. At week 3 PE during the initial branchial xenoma formation stage, there was a significant negative whole body net K + flux in Loma ‐exposed trout compared with other points during the exposure and subsequent infection. Additionally, Loma ‐exposed fish had marginally elevated plasma Na + and Cl − concentrations, whilst K + levels remained unchanged, compared with control fish. Although there was a progressive decrease in leucocrit, haematocrit remained unchanged over the course of the Loma exposure and subsequent infection. These results suggest that ionic compensation can occur at the gills during the development of xenomas during exposure to L. salmonae and the resultant infection, therefore allowing defence of plasma electrolyte concentrations, unlike the acute ionic disturbances seen with some other parasitic diseases.

EST database for early flower development in California poppy (Eschscholzia californica Cham., Papaveraceae) tags over 6000 genes from a basal eudicot - John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Laura M. Zahn; Lukas A. Mueller; Lena L. Landherr; Yi Hu; Daniel C. Ilut; Jennifer M. Arrington; Stephanie Choirean; Annette Becker; Dawn Field; et al. (Plant Molecular Biology, 2006)

Interaction of water temperature and challenge model on xenoma development rates for Loma salmonae (Microspora) in rainbow trout, Oncorhynchus mykiss (Walbaum) - J A Becker; D J Speare; I R Dohoo (Journal of Fish Diseases, 2006)
This study evaluated the regulatory effects of water temperature on the development of branchial xenomas caused by Loma salmonae using a high‐dose per os ‐challenge model compared with a low‐dose cohabitation‐challenge model. Approximately 275 juvenile rainbow trout (RBT), Oncorhynchus mykiss , were randomly distributed to six tanks with two tanks each maintained at 11, 15 and 19 °C. Fish in one tank from each temperature setting were exposed per os to macerated L. salmonae ‐infected gill material and fish in the other tank from each temperature setting were exposed to L. salmonae using the cohabitation‐challenge model. Fish were monitored for the development of branchial xenomas beginning at day 21 post‐exposure. Survival analyses were used to evaluate the effect of water temperature and challenge model on the number of days until the first visible branchial xenoma was detected. The survivor curves for the per os ‐challenge model revealed that there was at least one significant difference, whereas the cohabitation challenge did not reveal any significant differences amongst the temperature settings. The proportional hazards model revealed a significant interaction between the challenge model used and water temperature. This indicated that the effect of water temperature was different depending on challenge model. Additionally, from the mean xenoma intensities, on average, the per os ‐challenged fish showed higher xenoma intensity compared with the cohabitation‐challenged fish. Overall, the impact of water temperature on disease pathogenesis was greater when the RBT were per os challenged compared with using the cohabitation model.

Smooth pursuit rather than visual signals mediate short-term adaptation of the cervico-ocular reflex in humans - D. Mandellos; D. Anastasopoulos; W. Becker (Experimental Brain Research, 2006)

Site-specific recombination in Zea mays - S. Kerbach; H. Lörz; D. Becker (Theoretical and Applied Genetics, 2005)

Characterisation of the Dunaliella tertiolecta RbcS genes and their promoter activity in Chlamydomonas reinhardtii - T. L. Walker; D. K. Becker; C. Collet (Plant Cell Reports, 2005)

Influence of feeding ratio and size on susceptibility to microsporidial gill disease caused by Loma salmonae in rainbow trout, Oncorhynchus mykiss (Walbaum) - J A Becker; D J Speare; I R Dohoo (Journal of Fish Diseases, 2005)
Two trials were designed to quantify the effect of feeding ratio and fish size on the cohabitation transmission of Loma salmonae , the causative agent of microsporidial gill disease (MGD) in salmonids, Oncorhynchus spp. To evaluate the effect of feeding ratio on disease onset, groups of 45 rainbow trout, O. mykiss (Walbaum) (RBT), were fed daily at 1% (low), 2% (medium) or 4% (high) of the fish biomass in the tank. There were three tanks at each feeding level: two tanks were exposed to the pathogen and one was a control. For the second objective, 300 RBT were separated into seven tanks so that the weight classifications were small (17–23 g), medium (32–38 g) and large (57–63 g). Each size class was done in duplicate with one control tank containing medium‐sized fish. Separately for each trial, on day 0 post‐exposure (PE) five highly infectious RBT were added to each tank (not including the control tanks) to begin the cohabitation exposure period. Beginning on day 21 PE and continuing biweekly until days 70 and 77 PE for the feeding and fish size trials, respectively, each fish was evaluated for visible branchial xenomas to determine disease onset time. Using survival analysis, the survival curves for the low, medium and high feedings were not significantly different from each other. However, there were significant differences amongst the small, medium and large weight classes in the size trial. The median numbers of days to the development of branchial xenomas was 31, 38 and 42 for small, medium and large size fish, respectively. On any given day, a medium or large sized fish had a hazard ratio for developing branchial xenomas of 0.66 and 0.63, respectively, compared with a small fish. In addition to host species and host strain differences, fish size is now considered a host risk factor for the development of MGD.

Impacts of copepods on marine seston, and resulting effects on Calanus finmarchicus RNA:DNA ratios in mesocosm experiments - C. Becker; D. Brepohl; H. Feuchtmayr; E. Zllner; F. Sommer; C. Clemmesen; U. Sommer; M. Boersma (Marine Biology, 2005)

The genome of Desulfotalea psychrophila , a sulfate‐reducing bacterium from permanently cold Arctic sediments - R. Rabus; A. Ruepp; T. Frickey; T. Rattei; B. Fartmann; M. Stark; M. Bauer; A. Zibat; T. Lombardot; I. Becker; J. Amann; K. Gellner; et al. (Environmental Microbiology, 2004)
Summary Desulfotalea psychrophila is a marine sulfate‐reducing δ‐proteobacterium that is able to grow at in situ temperatures below 0°C. As abundant members of the microbial community in permanently cold marine sediments, D. psychrophila ‐like bacteria contribute to the global cycles of carbon and sulfur. Here, we describe the genome sequence of D. psychrophila strain LSv54, which consists of a 3 523 383 bp circular chromosome with 3118 predicted genes and two plasmids of 121 586 bp and 14 663 bp. Analysis of the genome gave insight into the metabolic properties of the organism, e.g. the presence of TRAP‐T systems as a major route for the uptake of C 4 ‐dicarboxylates, the unexpected presence of genes from the TCA cycle, a TAT secretion system, the lack of a β‐oxidation complex and typical Desulfovibrio cytochromes, such as c 553 , c 3 and ncc. D. psychrophila encodes more than 30 two‐component regulatory systems, including a new Ntr subcluster of hybrid kinases, nine putative cold shock proteins and nine potentially cold shock‐inducible proteins. A comparison of D. psychrophila 's genome features with those of the only other published genome from a sulfate reducer, the hyperthermophilic archaeon Archaeoglobus fulgidus , revealed many striking differences, but only a few shared features.

Temperature dependence of the polarized electronic absorption spectra of olivines. Part II?Cobalt-containing olivines - K. Ullrich; O. Ott; K. Langer; K. D. Becker (Physics and Chemistry of Minerals, 2004)

Ultraviolet light control of horizontal transmission of Loma salmonae - J A Becker; D J Speare (Journal of Fish Diseases, 2004)

Survey of Gastric Lesions and Blood Pepsinogen Levels in Pigs in Burkina Faso - H. Banga-Mboko; H. Tamboura; D. Maes; H. Traoré; I. Youssao; P.T. Sangild; B. El Amiri; B. Bayala; B. Remy; J.F. Beckers (Veterinary Research Communications, 2003)

Parasympathetic heart rate modulation during parabolic flights - F. Beckers; B. Seps; D. Ramaekers; B. Verheyden; A. E. Aubert (European Journal of Applied Physiology, 2003)

A promoter derived from taro bacilliform badnavirus drives strong expression in transgenic banana and tobacco plants - I. C. Yang; J. P. Iommarini; D. K. Becker; G. J. Hafner; J. L. Dale; R. M. Harding (Plant Cell Reports, 2003)

Elemental Composition of Liver and Kidney Tissues of Rough-Toothed Dolphins ( Steno bredanensis ) - E. A. Mackey; R. D. Oflaz; M. S. Epstein; B. Buehler; B. J. Porter; T. Rowles; S. A. Wise; P. R. Becker (Archives of Environmental Contamination and Toxicology, 2003)

Differential Transcriptional Regulation by Human Immunodeficiency Virus Type 1 and gp120 in Human Astrocytes - D Galey; K Becker; N Haughey; A Kalehua; D Taub; J Woodward; MP Mattson; A Nath (Journal of NeuroVirology, 2003)

Effects of monensin dose and treatment time on xenoma reduction in microsporidial gill disease in rainbow trout, Oncorhynchus mykiss (Walbaum) - J A Becker; D J Speare; J Daley; P Dick (Journal of Fish Diseases, 2002)
The objectives of the study were (1) to determine an acceptable dose of dietary monensin against microsporidial gill disease (MGD) of salmon caused by Loma salmonae and (2) to determine the life stage of L. salmonae at which the action of monensin was most effective at reducing clinical disease. Rainbow trout (RBT) were fed monensin diets at concentrations of 0, 10, 100, 1000 and 5000 ppm starting 1 week before per os exposure to L. salmonae infected gill material. Lethal sampling occurred at weeks 6, 7, 8 and 9 post‐exposure (PE). The acceptable dose of dietary monensin was determined to be 1000 ppm because it was the lowest concentration that produced a significant and constant reduction in xenoma formation. RBT were fed monensin at 1000 ppm beginning at 0, 1, 2 and 3 weeks before exposure and at 1, 2 and 3 weeks after exposure and continuing until week 9 PE. Fish in which treatment was initiated at the time of exposure or 1 week before, showed the greatest reduction in xenoma production when compared with the untreated RBT.

Temperature dependence of the polarized electronic absorption spectra of olivines. Part I - fayalite - K. Ullrich; K. Langer; K. D. Becker (Physics and Chemistry of Minerals, 2002)

Genetic variation of tocopherol content in a germplasm collection of Brassica napus L. - Fernando D. Goffman; Heiko C. Becker (Euphytica, 2002)

A Database for Volatile Organic Compounds - K. Mannschreck; K. Bächmann; K. H. Becker; Th. Heil; R. Kurtenbach; M. Memmesheimer; V. Mohnen; A. Obermeier; D. Poppe; R. Steinbrecher; Th. Schmitz; A. Volz-Thomas; et al. (Journal of Atmospheric Chemistry, 2002)

Iron in neurodegenerative disorders - D. Berg; G. Becker; P. Riederer; O. Rieß (Neurotoxicity Research, 2002)

HUMAN DUODENAL SPHEROIDS FOR NONINVASIVE INTRACELLULAR pH MEASUREMENT AND QUANTIFICATION OF REGULATION MECHANISMS UNDER PHYSIOLOGICAL CONDITIONS - MICHAEL WEINLICH; CHRISTINA BAUMSTARK; ENGIN USTA; HORST D. BECKER; MICHAEL J. SESSLER (In Vitro Cellular & Developmental Biology - Animal, 2002)

The nodulin VfENOD18 is an ATP-binding protein in infected cells of Vicia faba L. nodules - Jörg D. Becker; Leonilde M. Moreira; Dieter Kapp; S. Christian Frosch; Alfred Pühler; Andreas M. Perlick (Plant Molecular Biology, 2001)

Promoters derived from banana bunchy top virus-associated components S1 and S2 drive transgene expression in both tobacco and banana - S. Hermann; D. Becker; R. Harding; J. Dale (Plant Cell Reports, 2001)

High-yielding repetitive somatic embryogenesis and plant recovery in a selected tea clone, 'TRI-2025', by temporary immersion - A. Akula; D. Becker; M. Bateson (Plant Cell Reports, 2000)

The broad bean nodulin VfENOD18 is a member of a novel family of plant proteins with homologies to the bacterial MJ0577 superfamily - N. Hohnjec; H. Küster; U. Albus; S. C. Frosch; J. D. Becker; A. Pühler; A. M. Perlick; M. Frühling (Molecular Genetics and Genomics, 2000)

Abstracts of Presentations at the 21st congress of the Israeli phytopathological society February 14–15, 2000 ARO, the Volcani Center, Bet Dagan, Israel - S. Droby; G. Kritzman; A. Gamliel; Miriam Austerweil; Yael Skutelski; I. Peretz-Alon; E. Becker; J. Katan; R. Cohen; M. Edelstein; Carmela Horev; Y. Burger; et al. (Phytoparasitica, 2000)

Promoters derived from banana bunchy top virus DNA-1 to −5 direct vascular-associated expression in transgenic banana ( Musa spp.) - B. Dugdale; D. K. Becker; P. R. Beetham; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Linkage mapping and QTL analysis in coconut (Cocos nucifera L.) - A. Herrán; L. Estioko; D. Becker; M. J. B. Rodriguez; W. Rohde; E. Ritter (Theoretical and Applied Genetics, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Genetic transformation of Cavendish banana ( Musa spp. AAA group) cv 'Grand Nain' via microprojectile bombardment - D. K. Becker; B. Dugdale; M. K. Smith; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Genomic organization of the KIAA0057 gene that encodes a TRAM-like protein and its exclusion as a polycystic kidney and hepatic disease 1 (PKHD1) candidate gene - Luiz F. Onuchic; Michal Mrug; Alicia L. Lakings; Gabi Muecher; Jutta Becker; Klaus Zerres; Ellis D. Avner; Mehul Dixit; Stefan Somlo; Gregory G. Germino; Lisa M. Guay-Woodford (Mammalian Genome, 1999)

Cytoplasmic Effects on Pollen Embryogenesis Induction in Wheat Microspore Culture - P. A. Orlov; D. Becker; G. Shewe; H. Lörz (Cereal Research Communications, 1999)

Woody life-form composition and association on rainfall and soil fertility gradients in Ghana - Michael D. Swaine; Peter Becker (Plant Ecology, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Potential of active excretion of ammonia in three different haline species of crabs - D. Weihrauch; W. Becker; U. Postel; S. Luck-Kopp; D. Siebers (Journal of Comparative Physiology B, 1999)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Variability for the fatty acid composition of the seed oil in a germplasm collection of the genus Brassica - Leonardo Velasco; Fernando D. Goffman; Heiko C. Becker (Genetic Resources and Crop Evolution, 1998)

Active excretion of ammonia across the gills of the shore crab Carcinus maenas and its relation to osmoregulatory ion uptake - D. Weihrauch; W. Becker; U. Postel; S. Riestenpatt; D. Siebers (Journal of Comparative Physiology B, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Molecular wheat breeding by direct gene transfer - H. Lörz; D. Becker; S. Lütticke (Euphytica, 1998)

Broad immunocytochemical localization of the formylpeptide receptor in human organs, tissues, and cells - E. L. Becker; Faripour A. Forouhar; Margaret L. Grunnet; Francois Boulay; Marianne Tardif; Barbara-Jean Bormann; Darlene Sodja; Richard D. Ye; Joseph R. Woska Jr; Philip M. Murphy (Cell and Tissue Research, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Increasing incidence of colon and rectal cancer among Hispanics and American Indians in New Mexico (United States), 1969-94 - Ann Chao; Frank D. Gilliland; William C. Hunt; Marc Bulterys; Thomas M. Becker; Charles R. Key (Cancer Causes & Control, 1998)

Inhibition of Na + /K + -ATPase and of active ion-transport functions in the gills of the shore crab Carcinus maenas induced by cadmium - U. Postel; G. Petrausch; S. Riestenpatt; D. Weihrauch; W. Becker; D. Siebers; J. Malykh (Marine Biology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Localization of introduced genes on the chromosomes of transgenic barley, wheat and triticale by fluorescence in situ hybridization - C. Pedersen; J. Zimny; D. Becker; A. Jähne-Gärtner; H. Lörz (Theoretical and Applied Genetics, 1997)

Efficient transformation of scutellar tissue of immature maize embryos - R. Brettschneider; D. Becker; H. Lörz (Theoretical and Applied Genetics, 1997)

Molecular cloning and mapping of a novel developmentally regulated human C2H2-type zinc finger - Kevin G. Becker; Rachel D. Canning; James W. Nagle; Anindya M. Dehejia; Mihael H. Polymeropoulos; Insong J. Lee; Ameer M. Gado; William E. Biddison; Paul D. Drew (Mammalian Genome, 1997)

Recognition of visual stimuli from multiple neuronal activity in monkey visual cortex - J. D. Becker; J. Krüger (Biological Cybernetics, 1996)

Recognition of visual stimuli from multiple neuronal activity in monkey visual cortex - J. D. Becker; J. Krger (Biological Cybernetics, 1996)

Degradation of 4-chloro-2-methylphenol by an activated sludge isolate and its taxonomic description - U. Lechner; R. Baumbach; D. Becker; V. Kitunen; G. Auling; M. Salkinoja-Salonen (Biodegradation, 1995)

Analysis, classification, and coding of multielectrode spike trains with hidden Markov models - G. Radons; J. D. Becker; B. Dülfer; J. Krüger (Biological Cybernetics, 1994)

Analysis, classification, and coding of multielectrode spike trains with hidden Markov models - G. Radons; J. D. Becker; B. Dlfer; J. Krger (Biological Cybernetics, 1994)

Differences in mercury contamination and elimination during feather development in gull and tern broods - P.H. Becker; D. Henning; R.W. Furness (Archives of Environmental Contamination and Toxicology, 1994)

Ultrastructural studies on a chlorella virus from Germany - B. Becker; D. E. Lesemann; W. Reisser (Archives of Virology, 1993)

Neurovirulence of herpes simplex virus type 1 depends on age in mice and thymidine kinase expression - T. Ben-Hur; Julia Hadar; Y. Shtram; D. H. Gilden; Y. Becker (Archives of Virology, 1983)

Microtubular reaction in human fibroblasts infected by cytomegalovirus - G. Pfeiffer; D. Willutzki; D. Weder; B. Becker; K. Radsak (Archives of Virology, 1983)

A low thymidine kinase-producing mutant of herpes simplex virus type 1 causes latent trigeminal ganglia infections in mice - Y. Gordon; D. H. Gilden; Y. Shtram; Y. Asher; E. Tabor; M. Wellish; M. Devlin; D. Snipper; J. Hadar; Y. Becker (Archives of Virology, 1983)

Examination of procedures for acute toxicity tests with the fathead minnow and coal synfuel blends - C. D. Becker; D. W. Crass (Archives of Environmental Contamination and Toxicology, 1982)

Klinik, Toxikologie und Therapie einer schweren Carbromalvergiftung mit letalem Ausgang - H. Gruska; V. Becker; K. -H. Beyer; J. Hsten; St. Kubicki; D. Weiss (Archives of Toxicology, 1970)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)